New strategy for prolonging the preservation time of hearts for transplantation - Mesáros, S; Grunfeld, S; Mesárosová, A; Malinski, T (Physiological research, 1997)
Our study concerned the findings that rat and rabbit heart transplants do not survive after six hours. They become dark, hard and fail to contract within 2 min after reperfusion and never regain their function. We tested the supplementation of solutions for heart transplant preservation with tetrahydrobiopterin (H4B) and L-arginine (L-ARG) to maintain the oxidative and reductive domains of the endocardial NO synthase. We decided to study the excised rabbit hearts preserved in Hank's balanced salt solution (HBSS) at 0 degrees C supplemented with different concentrations of H4B (0, 1, 5, 10 or 100 microM). At desired time intervals, successive pieces stored in the above solutions were warmed to rabbit body temperature in 4 ml of HBSS and maximally agonized by direct application of 20 microl of 200 microM bradykinin (or other agonist) onto the exposed endocardium. Nitric oxide bursts were monitored with a porphyrinic NO sensor lying on the exposed endocardium. Our goal was to find the lowest H4B concentration which would maximally agonize NO. and prolong the time of heart preservation to more than 6 hours. Ten microM are a minimum H4B concentration which achieves maximum prolongation of heart preservation time up to 90 hours. This effect was based upon maximal potentiation of NO. release and minimizing of superoxide production.
Keywords: Time Factors; Rabbits; Animals; Isotonic Solutions; Heart Transplantation; uchovávání tkání; Nitric Oxide Donors; Tissue Preservation; časové faktory; donory oxidu dusnatého; Heart; roztoky pro uchovávání orgánů; krysa rodu Rattus; Rats; srdce; Organ Preservation Solutions; zvířata; transplantace srdce; isotonické roztoky; králíci